Duloxetine for the Management of Diabetic Peripheral Neuropathic Pain: Evaluation of Functional Outcomes - Armstrong, David G.; Chappell, Amy S.; Le, Trong K.; Kajdasz, Daniel K.; Backonja, Miroslav; D'Souza, Deborah N.; Russell, James M. (Pain medicine (Malden, Mass.), 2007)
ABSTRACT Objective.  To assess the effectiveness of duloxetine, compared with placebo, on patient‐reported health outcomes over a 12‐week period, in the management of diabetic peripheral neuropathic pain (DPNP). Methods.  The results were pooled from three 12‐week multicenter, double‐blind studies. In study 1 (N = 457), patients with DPNP were randomly assigned to treatment with duloxetine 20 mg once daily (QD), 60 mg QD, 60 mg twice daily (BID), or placebo. In studies 2 (N = 334) and 3 (N = 348), patients with DPNP were randomly assigned to treatment with duloxetine 60 mg QD, 60 mg BID, or placebo. Patient‐reported functional outcomes were measured by the Short Form 36 (SF‐36), the interference portion of the Brief Pain Inventory (BPI), and EuroQol 5D Health Questionnaire (EQ‐5D). Results for all functional outcomes from the intent‐to‐treat and completer populations are discussed. Results.  In the SF‐36 health survey and the BPI interference, duloxetine 60 mg QD and 60 mg BID were significantly superior to placebo in all the domains (P ≤ 0.03). In the analysis of the EQ‐5D, duloxetine 60 mg QD (P = 0.004) and 60 mg BID (P < 0.001) were significantly better than placebo on all items. Conclusions.  Acute treatment with duloxetine was associated with significant improvement in functional outcomes in persons with DPNP.